Impact of phase shifting transformers on distance protection and fault ride-through scheme - Tao Zheng; Jiaxu Yu; Xiaoxiao Liu; You Shen; Chengxi Sui (International Journal of Electrical Power & Energy Systems)
The phase shifting transformer (PST) serves as an important power flow control device that adjusts power flow by altering the phase of voltages at its terminals. This adjustment can affect the distance protection of lines equipped with PST, potentially leading to mal-operation of distance protection. To address this issue, this paper analyzes the impact of a PST on the calculated impedance of the distance relay and conducts a detailed analysis of the adaptability of distance protection in lines equipped with a PST, revealing that the phase shifting range is the primary factor affecting distance protection. The analysis indicates that the impact of small phase-shifting adjustments (within ± 10°) on distance protection is little, while large phase-shifting adjustments (beyond ± 10°) can lead to mal-operation. To deal with the challenges caused by large phase-shifting adjustments, a novel fault ride-through (FRT) scheme that employs an additional hardware loop is proposed in this paper. When a line fault is occurred, the additional hardware loop is triggered to ensure the quick isolation and safety of the PST. This FRT scheme guarantees that distance protection functions correctly, even during large phase-shifting adjustments. The effectiveness and feasibility of the proposed scheme are validated through simulations.